MILLENIAL INVESTORS IN CIANJUR: FUNDAMENTAL ANALYSIS AND OVERCONFIDENCE IN DECISION MAKING - Fauzi Fauzi; Rita Irviani (Universitas 45 Surabaya, 2023)
This study's objective is to examine how fundamental analysis and overconfidence affect millennial investors in Cianjur's investment choices. This study uses quantitative research techniques, and the investors in the Cianjur region were given questionnaires to complete. 71 Cianjur young investors were sampled for this study using a purposive sampling method. The analytical approach uses hypothesis testing, multiple linear regression analysis, and the conventional assumption test. The results of this study demonstrate that overconfidence has a significant impact on investment decisions made by millennial investors in Cianjur, but fundamental analysis has no significant impact on those decisions. Fundamental analysis also has a significant impact on investment. Cianjur's millennial investors make choices.